Hedge over heels - McMullen-Ciotti, Elise (2022)
Rayna is used to being the new kid at school. But that doesn't mean she wants to make new friends! Why bother when the military will only reassign her mom again soon anyway? No, the only friend Rayna wants is a furry, four-legged one. But instead of the dog she's been dreaming of, what Rayna gets is a hedgehog named Spike who is as prickly and emo as she is. Worse, Rayna's mom insists she enter Spike in a pet talent show to get to know some kids her age, including a very cute boy named Nick. Only Spike doesn't want to hang out or show off any more than Rayna does. Will Rayna curl herself into a ball and hide, or will she and Spike take a chance a new pack of friends?
ages 8-12
Keywords: Middle school girls -- Juvenile fiction; Children of military personnel -- Juvenile fiction; Hedgehogs -- Juvenile fiction; Talent shows -- Juvenile fiction; Friendship -- Juvenile fiction; Infatuation -- Juvenile fiction; Friendship -- Fiction; Children of military personnel -- Fiction; Schools -- Fiction; Hedgehogs -- Fiction; Children of military personnel; Friendship; Hedgehogs; Infatuation; Middle school girls; Talent shows; Fiction; Juvenile works; School fiction; School fiction